Practice insights – Experimentation and design thinking in Public policy-making processes - James Origa Otieno (ZBW – Leibniz Information Centre for Economics, 2019)
Policy-making is a complex iterative process that requires engagement with a multiplicity of actors facing different incentives and constraints underpinned by differing structural and institutional variables. Design-thinking as a human-centered approach to problem solutioning offers valuable lessons that policy makers would find useful. This article, presented as a policy practice insight note, posits that the focus of policy design shouldn't be so much on what makes a technically superior alternative, but what makes an institutionally sound approach and crowds in policy implementers and recipients from the design stage. It presents an understanding that policy design is more about creating processes that elicit information and feedback on government interventions than about getting the objectives right at the beginning thus allowing for an experimentation approach to policy design. The paper concludes that for policy design to be effective, finding a contextual best fit is more desirable than blanket adoption of “global best practices”
Keywords: Z18; 320; Design thinking; Experimentation; Public Policy design